PENINGKATAN KEMAMPUAN MENGENAL LAMBANG BILANGAN MELALUI PERMAINAN ULAR TANGGA PADA ANAK USIA 5-6 TAHUN DI TK ISLAM AISYAH MUARA PENIMBUNG ULU (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to improve the ability to recognize number symbols in children aged 5-6 years at TK Islam Aisyah Muara Penimbung Ulu through the use of snakes and ladders game media. The primary problem identified was the low understanding of number symbol concepts, where children tended to memorize without understanding the meaning of the symbols. The method used is Classroom Action Research (CAR) following the Kemmis & McTaggart model, consisting of two cycles. The research subjects consisted of 12 children. The results showed a significant increase in children's cognitive abilities, rising from a low completion rate in the pre-cycle stage to 49.6% in Cycle I, and reaching 80.47% in Cycle II. It is concluded that the use of the snakes and ladders game is effective as an interactive and concrete learning medium in transforming abstract mathematical concepts into an enjoyable learning experience for children.